What Contributes to Rising Inequality in Large Cities? - Luis Ayala; Javier Martín-Román; Juan Vicente Perdiz (Luxembourg Income Study (LIS), 2023)
This paper aims to analyze the trends in income inequality in large cities within a selected sample of OECD countries. Specifically, we consider a set of determinants that account for changes in the income distribution and estimate their contributions to inequality by developing both a dynamic approach -differences in inequality in large cities over the last two decades- and a static approach -differences in inequality between large cities and other areas. We use a combination of reweighting techniques and recentered influence functions (RIF) to detect both an upward trend in inequality within large cities and higher levels of inequality with respect to other areas. These results are mainly driven by changes in the returns to endowments rather than by changes in its distribution. We also find that the results are not of the same magnitude across the countries analysed. The contribution to inequality of the skill premium is considerably higher in the US than in European countries.
Keywords: D31; P52; R12; 330; large cities; income inequality; counterfactual analysis; RIF-OLS decomposition